Vitamin D supplementation is associated with higher serum 25OHD in Asian and White infants living in Vancouver, Canada. Issue 2 (15th October 2012) - Green, Tim J.; Li, Wangyang; Barr, Susan I.; Jahani, Mitra; Chapman, Gwen E.
Abstract To prevent rickets, the Health Canada and the American Academy of Pediatrics recommend that breastfed infants receive a daily vitamin D supplement of 10 μg d−1. Compliance with this recommendation is variable and its effect on infant vitamin D status is unclear. We measured serum 25‐hydroxyvitamin D (25OHD) in Asian immigrant (n = 28) and White (n = 37) mothers and their infants aged 2–4 months living in Vancouver (49°N). Mothers completed health and demographic questionnaires. All subjects were term infants who were primarily breastfed. Analysis of variance, χ2, multiple regression and logistic regression analysis were performed as appropriate. Mean 25OHD of the infants was 31 (95% confidence interval 28–34) ng mL−1. Only two infants had a 25OHD concentration indicative of deficiency, <10 ng mL−1. Of the infants, 14% (n = 9) and 49% (n = 32) were vitamin D insufficient based on two commonly used cut‐offs of 20 and 30 ng mL−1, respectively. Fifty‐eight (89%) infants had been given a vitamin D supplement. Mean 25OHD was 9.4 ng mL−1 higher in infants consuming ≥10 μg d−1 of vitamin D from supplements vs. those consuming less (P = 0.003). Mother's 25OHD, season, skin colour or ethnicity (Asian vs. White) did not influence infant 25OHD. The infants in our study, most of whom received vitamin D supplements, were generally protected against low 25OHD. The study was limited by sample size and the nature of the cross‐sectional study design.